2017
DOI: 10.1039/c7cc02310c
|View full text |Cite
|
Sign up to set email alerts
|

Selective adsorption of carbohydrates and glycoproteins via molecularly imprinted hydrogels: application to visible detection by a boronic acid monomer

Abstract: Selective adsorption of carbohydrates and glycoproteins was effectively achieved by molecularly imprinted hydrogels (MIHs) with a poly(ethylene glycol) (PEG)-based crosslinker and 4-vinylphenylboronic acid. In addition, an MIH with a novel boronic acid monomer provided selective adsorption and enabled visible detection of fructose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…All azoBs were synthesized by diazo-coupling reactions between the corresponding amine precursor compounds and phenylboronic acid derivatives (see the Experimental Section and Scheme S1 in the Supporting Information). The synthesized products were confirmed by 1 H and 13 C NMR (Figures S1 and S2, respectively), ESI-MS, and elemental analysis. Some of the azoBs were characterized using high-resolution mass spectroscopy instead of elemental analysis.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…All azoBs were synthesized by diazo-coupling reactions between the corresponding amine precursor compounds and phenylboronic acid derivatives (see the Experimental Section and Scheme S1 in the Supporting Information). The synthesized products were confirmed by 1 H and 13 C NMR (Figures S1 and S2, respectively), ESI-MS, and elemental analysis. Some of the azoBs were characterized using high-resolution mass spectroscopy instead of elemental analysis.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
“…Electrospray ionization mass spectra (ESI-MS) were recorded by using a JEOL Accu-TOF JMS T100-CS. 1 H, 13 C, and 11 B NMR spectra were measured at 25 °C with a Bruker Avance 400 spectrometer. Elemental analyses for C, H, and N atoms were performed on a Perkin Elmer series II CHNS/ O Analyzer 2400.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results also showed that the composition and ratio of imprinted polymers affected the quality of glycoprotein imprinting, and that HRP‐imprinted silica nanomaterials could recognize HRP from spiked human serum. Kubo et al developed the PEG‐based molecularly imprinted hydrogels (MIHs) with VPBA as functional monomer and HRP, fetuin and ribonuclease B (RNase B) as templates . Moreover, they originally prepared a functional monomer that was inclusive of an azo group and aromatic boronic acid (denoted as VAAB) for fabricating fructose‐MIHs.…”
Section: Nanomaterials In Glycoproteomicsmentioning
confidence: 99%
“…[10][11][12][13] Zhai et al reported electrochemical imprinted sensors for the determination of ascorbic acid. Nanofiber membranes of cellulose acetate/ multi-walled carbon nanotubes/polyvinylpyrrolidone were prepared by an electrospinning technique.…”
mentioning
confidence: 99%